1999
DOI: 10.1007/s004320050286
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the p53 gene on the in vitro chemosensitivity of colorectal cancer cells

Abstract: Routine assessment of p53 status may be helpful in selecting patients with the wildtype p53 gene, who have a predictably better response to chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Immunostaining does not necessarily distinguish the accumulation of abnormal p53 protein due to gene mutation from the overexpression of normal protein (Lenz, Hayashi et al, 1998, Momand, ANNALS OF Cancer Research andTherapy Zambetti et al, 1992). In fact, it has been reported that mutation or disruption of the p53 gene is associated with low chemosensitivity to 5-FU (Bunz, Hwang et al, 1999, Zheng, Wang et al, 1999. p53-independent regulation of apoptosis in colorectal cancers has been shown in the previous in vitro studies (Bracey, Miller et al, 1995).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Immunostaining does not necessarily distinguish the accumulation of abnormal p53 protein due to gene mutation from the overexpression of normal protein (Lenz, Hayashi et al, 1998, Momand, ANNALS OF Cancer Research andTherapy Zambetti et al, 1992). In fact, it has been reported that mutation or disruption of the p53 gene is associated with low chemosensitivity to 5-FU (Bunz, Hwang et al, 1999, Zheng, Wang et al, 1999. p53-independent regulation of apoptosis in colorectal cancers has been shown in the previous in vitro studies (Bracey, Miller et al, 1995).…”
Section: Discussionmentioning
confidence: 90%
“…p53 protein normally functions as either an initiator of repair of the damaged sense DNA or a trigger of the apoptotic pathway if a sufficient level of damage takes place within the cell (Harwood, Frazier et al, 1996, Leonard, Canman et al, 1995. Inactivation or mutation of the p53 gene is allegedly associated with the enhancement of cellular resistance to DNA-damaging agents (Benhattar, Cerottini et al, 1996, Bunz, Hwang et al, 1999, Lowe, Schmitt et al, 1993, Zheng, Wang et al, 1999. It has been suggested that the p53 gene assay can be employed to predict the responsiveness of cancer to chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical studies have revealed higher resistance to fluoropyrimidine therapy of tumors expressing p53 mutants (Benhattar et al, 1996;Cabelguenne et al, 2000;Zheng et al, 1999). In several cases such effects of p53 mutants were attributed to dominant-negative suppression of the wild type p53 activity that resulted in abrogation of p53-induced apoptosis (Bunz et al, 1999), and an increase in activity of the MDR1 gene (Bottini et al, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…[160][161][162][163][164][165][166][167][168] Here, we will only briefly report on the putative role of p53 with respect to 5-FU efficacy, as this relationship has been most extensively studied. Mutations in the p53 gene and p53 overexpression have been associated with 5-FU chemoresistance both in vitro [169][170][171] and in vivo in colorectal, 124,[172][173][174][175] head and neck, 176,177 and breast cancer. 178 However, results in some other studies are less unequivocal.…”
Section: Jg Maring Et Almentioning
confidence: 99%